ANALISIS MAJAS SINDIRAN PADA DEBAT CALON PRESIDEN PERTAMA TAHUN 2024 DALAM KANAL YOUTUBE - Ari Musdolifah; Anugrah Febriyani; Christopher Immanuel Enggar Pardede; Citra Swastanti Anggraeni; Dilla Novita Devi Selviana (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to analyze the use of satirical language styles in the first presidential candidate debate in 2023. The research method used is descriptive qualitative by taking data from transcripts of debate videos available on the YouTube channel. The satirical language styles analyzed include cynicism, innuendo, irony, sarcasm, satire, and antifrasis. The data collection technique used is look and note, where the researcher pays attention and notes sentences that contain innuendo. The results of the analysis show that the satirical language style is used with various meanings and purposes, such as criticizing political opponents, conveying messages indirectly, or for entertainment purposes. This research provides a deeper understanding of the use of satirical language in political communication, as well as its implications in influencing public opinion.